A paradigm shift in cystic fibrosis nutritional care: clinicians' views on the management of patients with overweight and obesity - Snowball, JE; Flight, WG; Heath, L; Koutoukidis, DA (Elsevier, 2023)
Background: Overweight and obesity among people with cystic fibrosis (pwCF) has become more prevalent since the widespread adoption of CF transmembrane conductance regulator (CFTR) modulator therapies and presents a new challenge for nutritional care. We aimed to explore how clinicians working in CF care approach the management of adults with overweight and obesity.